Slave emancipation and transformations in Brazilian political citizenship - Castilho, Celso Thomas (Pitt Latin American series., 2016)
"Castilho offers original perspectives on the political upheaval surrounding the process of slave emancipation in postcolonial Brazil. He shows how the abolition debates in Pernambuco transformed the practices of political citizenship and marked the first instance of a mass national political mobilization"--